2020
DOI: 10.1016/j.mayocp.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Diabetic Kidney Disease

Abstract: While the global prevalence of both type 1 and type 2 diabetes mellitus is similar in men and women, the consequences of diabetes on associated end-organ complications, including diabetic kidney disease appear to be more sex-specific. Particularly, women with diabetes have higher mortality rates for diabetes-related deaths, and higher prevalence of diabetic kidney disease risk factors such as hypertension, hyperglycemia, obesity, and dyslipidemia. However, the evidence for the impact of sex on diabetic kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 101 publications
(181 reference statements)
1
39
2
9
Order By: Relevance
“…Although the prevalence of DM appears to be similar between both sexes, women with DM have a higher residual lifetime risk at all ages; a higher mortality rate from diabetes‐related deaths, including diabetic nephropathy; and a higher prevalence of risk factors for diabetic nephropathy 51 . However, there are controversial studies regarding the risk of diabetic nephropathy according to sex, such as if there is a greater risk in men, 52 or in women, and even in other studies, no differences by sex have been found, as was clearly detailed by Maric‐Bilkan 51 . The reasons for these inconsistent findings include different populations of patients studied, age, type of diabetes, hormonal status, hormone replacement and the proportion of menopausal women vs young women.…”
Section: Sexual Dimorphism In Chronic Renal Diseasesmentioning
confidence: 99%
“…Although the prevalence of DM appears to be similar between both sexes, women with DM have a higher residual lifetime risk at all ages; a higher mortality rate from diabetes‐related deaths, including diabetic nephropathy; and a higher prevalence of risk factors for diabetic nephropathy 51 . However, there are controversial studies regarding the risk of diabetic nephropathy according to sex, such as if there is a greater risk in men, 52 or in women, and even in other studies, no differences by sex have been found, as was clearly detailed by Maric‐Bilkan 51 . The reasons for these inconsistent findings include different populations of patients studied, age, type of diabetes, hormonal status, hormone replacement and the proportion of menopausal women vs young women.…”
Section: Sexual Dimorphism In Chronic Renal Diseasesmentioning
confidence: 99%
“…An increasing amount of studies have investigated the effect of sex differences on DKD development and progression, however, but different cohorts have reported conflicting findings. In studies that enrolled patients with type 2 diabetes, it seems that more results indicated female has greater risk of DKD progression [8] . A study from Japan [12] (247 male and 97 female)…”
Section: Discussionmentioning
confidence: 99%
“…However, noninvasive available markers for accurate prediction and diagnoses of DN in diabetic patients are lacking now ( 8 ). It is worth noting that many studies have found the burden of diabetes is different in different genders ( 9 , 10 ). For example, women have higher mortality rate for diabetes-related deaths, including DN ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that many studies have found the burden of diabetes is different in different genders ( 9 , 10 ). For example, women have higher mortality rate for diabetes-related deaths, including DN ( 9 ). One may speculate that there is maybe something different in pathology and predictors of DN between men and women.…”
Section: Introductionmentioning
confidence: 99%